Pengaruh Struktur Modal, Ukuran Perusahaan dan Keputusan Investasi Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Mutiara, Mutiara; Negara, Iwan Kusuma; Wardani, Laila (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This study aims to analyze the effect of Capital Structure, Company Size, and Investment Decisions on Firm Value with Profitability as an Intervening variable in Food and Beverage Subsector Companies listed on the Indonesia Stock Exchange for the 2018-2022 Period. The type of research used in this study is associative with a quantitative approach. The data collection method uses a survey sample. The population in this study amounted to 26 companies. Data analysis techniques using path analysis and multiple linear regression analysis. The results of this study indicate that Capital Structure has a negative and significant effect on Firm Value, Company Size and Profitability have a significant positive effect on firm value while Investment Decisions have a positive and insignificant effect on Firm Value. Capital Structure has a negative and significant effect on Profitability, while Company Size and Investment Decisions have a positive and insignificant effect on Profitability. While Profitability as an intervening variable is able to mediate Capital Structure, while Profitability as an intervening variable is unable to mediate Company Size and Investment Decisions on Firm Value.